2020
DOI: 10.1177/1076029620977910
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Patents With Lung Cancer

Abstract: Lung cancer is the leading cause of death from cancer in Japan. Studies in other countries have reported a venous thromboembolism (VTE) rate of 4%–20% in cancer patients. In this study, we aimed to determine the incidence of VTE in lung cancer patients in Japan and compared the characteristics of patients with and without VTE. In this retrospective cohort study, the clinicopathological characteristics of study patients with and without concomitant VTE were compared. Patients with lung cancer treated at Fukui P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 18 publications
3
33
0
Order By: Relevance
“…These findings agreed with the data of other studies indicating that most thromboembolic events in patients with lung cancer undergoing chemotherapy occur within 6 months after diagnosis. 3 …”
Section: Risk Factors and Biomarkers Of Lung Cancer-associated Vtementioning
confidence: 99%
See 2 more Smart Citations
“…These findings agreed with the data of other studies indicating that most thromboembolic events in patients with lung cancer undergoing chemotherapy occur within 6 months after diagnosis. 3 …”
Section: Risk Factors and Biomarkers Of Lung Cancer-associated Vtementioning
confidence: 99%
“…These findings agreed with the data of other studies indicating that most thromboembolic events in patients with lung cancer undergoing chemotherapy occur within 6 months after diagnosis. 3 Therapy-Related Risk Factors Surgery A prospective study investigating blood coagulation in lung cancer patients and benign lung disease patients indicated that both patients with lung lobes in a hypercoagulable state pre-and post-operation were prone to thrombosis. 32 In a retrospective study, 232 patients undergoing lung cancer surgery were investigated in detail, and of these 5.2% developed VTE after 60 days.…”
Section: Clinical Stage and Time Interval After Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple causes, such as an overexpression of tissue factor, thrombocytosis, leukocytosis, anemia, infection, old age, circulatory stasis, and immobilization, may contribute to the occurrence of TEE in patients with cancer 10 , 23 26 . Furthermore, the administration of anti-cancer drugs, especially platinum compounds, the essential agents for adjuvant chemotherapy for NSCLC, is associated with the risk of TEE 9 12 , 18 , 25 , 26 . Although the mechanisms of platinum-induced hypercoagulability are not entirely clear, several reports have suggested possible pathophysiologic processes such as vascular endothelial cell damage and necrosis, platelet activation and aggregation, and increased procoagulant activity 11 , 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the risk of TEE can increase with the administration of chemotherapy 9 11 . TEEs have been reported in patients with NSCLC receiving palliative chemotherapy or those with small cell lung cancer (SCLC) in several studies 9 , 12 20 . However, there were very few reports about TEEs in NSCLC patients who underwent adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%